Grateful in the Scroll Era: Kontribusi Gratitude terhadap Social Comparison pada Mahasiswa yang Mengakses Media Sosial - Messy Mardatillah; Rahmadianti Aulia (Lembaga Yasin AlSys, 2026)
Intensive use of social media among university students has the potential to increase tendencies toward social comparison, which may negatively affect psychological well-being. One protective factor that may reduce this tendency is gratitude. This study aimed to analyze the contribution of gratitude to social comparison among university students who use social media. A quantitative approach was employed using simple linear regression with a sample of 401 students obtained through accidental sampling. Data were collected using a modified Gratitude Questionnaire-6 (GQ-6) and a social comparison scale encompassing upward comparison and downward comparison dimensions. The results showed that gratitude contributed negatively and significantly to social comparison, accounting for 4.1% of the variance in upward comparison and 4.4% in downward comparison. Descriptively, students’ gratitude levels were in the moderate category, upward comparison tended to be low, and downward comparison fell within the moderate category. These findings indicate that the higher students’ gratitude, the lower their tendency to engage in social comparison on social media. The implications underscore the importance of strengthening gratitude as a preventive effort to help students use social media more adaptively and to support their psychological well-being.